Endovascular Surgery for Ruptured Aneurysms with Vasospasm - Kurata, A. (Centauro S.r.l., 2007)
With the existence of vasospasm, it is recommended that direct clipping surgery for a ruptured aneurysm be delayed until its disappearance, but this may be associated with aneurysmal re-rupture resulting in a poor outcome for the patients. Indications for endovascular coil embolization in such cases are discussed. Since November in 2003, we have applied endovascular coil embolization in 11 consecutive patients with ruptured aneurysms and apparent vasospasm of the parent artery from two to 17 days (average: eight days) after initial subarachnoid hemorrhage. Three patients had aneurysmal re-rupture before treatment, but the other eight had only experienced the one episode of subarachnoid hemorrhage. With one exception, all endovascular procedures could be successfully performed, resulting in complete occlusion of aneurysms and remarkable dilatation of inserted spastic vessels without technical complications or aneurysmal re-rupture. For the one case of failure because of a tortuous artery, direct clipping surgery was performed after disappearance of vasospasm. Cerebral infarction occurred in four, but only one correlated with the distribution of catheterization, and neurological deficits had completely disappeared three months after the onset. This preliminary report concerning a small number of patients suggests that endovascular coil embolization is not contra-indicated for aneurysms with vasospasm requiring catheterization. A large study for confirmation is now warranted.